Urgensi Penerapan Dasar-Dasar Kepemimpinan Al-Qur’an di Lembaga Pendidikan Islam - Didy Setiawan; Moh Irwansyah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Leaders in educational institutions play a crucial role in achieving goals; however in reality, leaders who hinder the goal attainment process with unethical behaviors such as corruption and persecution are still prevalent. Therefore, implementing the leadership principles found in the Qur'an is a crucial key for educational leaders to efficiently fulfill their tasks. The aims of this study is to clarify the basic principles of the leadership of the Qur'an, including the definition and urgency of its implementation in Islamic educational institutions. The Systematic Literature Review (SLR) method is used in this research, which is to collect and analyze data from a variety of literature, including books, journal articles, and other related sources. This is the conclusion of this study: 1) There are various terms of leadership in the Qur'an, such as caliphs, priests, ulil amri, qawwam, sultan, malik, and za'im. In Islam, the ideal leader is someone who overlooks the character of the Prophet SAW and conducts his leadership by obeying the principles of the Quran leadership. 2) Applying the basics of the Quran leadership is essential to form a religious leader who is fearful, responsible, integrity, justice, and caring for his subjects. Thus, this leadership can support the Islamic educational institutions in achieving their goals efficiently and effectively.